2021
DOI: 10.1002/jcb.30191
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of miR‐1290 in cancer progression, diagnosis, prognosis, and treatment: An oncomiR or onco‐suppressor microRNA?

Abstract: Cancer is one of the leading causes of death in humans because of the lack of early diagnosis, distant metastases, and the resistance to adjuvant therapies, including chemotherapy and radiotherapy. In addition to playing an essential role in tumor progression and development, microRNAs (miRNAs) can be used as a robust biomarker in the early detection of cancer. MiR‐1290 was discovered for the first time in human embryonic stem cells, and under typical physiological situations, plays an essential role in neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 164 publications
(380 reference statements)
0
8
0
Order By: Relevance
“…Targeting miRNAs for cancer therapy has gained increasing attention in recent years, our current data highlighted that miR-1290 had an important effect on promoting PC cell growth both in vivo and in vitro. Importantly, miR-1290 is proposed as a potential diagnostic and therapeutic target in many cancers, and miR-1290 seems to regulate a wide spectrum of genes involved in cancer development and chemoresistance (Kalhori et al, 2021). Therefore, targeting miR-1290 might be the possible treatment to hinder the progression of in prostate cancer in clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting miRNAs for cancer therapy has gained increasing attention in recent years, our current data highlighted that miR-1290 had an important effect on promoting PC cell growth both in vivo and in vitro. Importantly, miR-1290 is proposed as a potential diagnostic and therapeutic target in many cancers, and miR-1290 seems to regulate a wide spectrum of genes involved in cancer development and chemoresistance (Kalhori et al, 2021). Therefore, targeting miR-1290 might be the possible treatment to hinder the progression of in prostate cancer in clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular mechanism studies have revealed that CagA, the main virulence factor of H. pylori , primarily induces inflammation in gastric mucosal epithelial cells and alters cell pyroptosis signalling, leading to stomach lesions 3 . The regulatory mechanism involving miRNA-1290 may play a crucial role in this process and thus holds diagnostic value as a potential tumour marker 4 . This review analyzed the dual action pattern of pyroptosis, which might also play distinct roles in other cancers beyond GC while exhibiting signalling pathways specific to each type of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a group of small non-coding RNAs (∼21 nucleotides) that could regulate posttranscriptionally gene expression by degrading mRNAs or inhibiting its translation. MiRNAs have a signi cant effect on regulating molecular signaling pathways so that disorder in miRNAs expression can lead to the progression and development of cancerous and non-cancerous diseases [1,2]. Moreover, the expression of miRNAs plays an essential role in regulating innate and adaptive immune system activity.…”
Section: Introductionmentioning
confidence: 99%
“…This miRNA was rst found in human embryonic stem cells, which plays an essential role in developing the fetal nervous system [7]. Our previous report shows that miR-1290 is overexpressed in numerous cancers such as colorectal, breast, stomach, esophageal squamous cell carcinoma, pancreatic, and lung cancer [2]. Therefore, its oncogenic activity bene ts developing cancer, metastasis, and even resistance to treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation